Rancangan Pembukuan Akuntansi Berbasis Excel for Accounting Pada Koperasi Jasa Keuangan Syariah (KJKS) - Chandra, Novrina; Sukartini (Akuntansi dan Manajemen, 2015)
In order to increase the society empowerment, Government of Padang create a program PKBK-BMT. This program is an integrated activity in order to accelerates poverty reduction, so that thegovernment of Padang form KJKS-BMT in every districts which aims to facilitates the poor society with microfinance and sustainable assistance, so that they can empower themselves. KJKS must convey accountability and financial reports activities to the local government. Therefore it needs accountable, accurate and timely financial statement. Both partners in these activities together are equaly have very good potential business development, but lack in the processing of financial transaction data and in the preparing of qualified financial statement for the decision making process of business development accountability.The results of this activitiy are the design of accounting bookkeeping based on excel for accounting, creating administrators who has ability to operate financial database, analizing and inputting financial transaction on the design of application. Beside, administrators can get the latest financial information at anytime by accessing that application design. The goals are to be known how far this program will run well and if there are some constraints encountered in the field then can immediately discussed with the administrators from both partners.